Effective engagement in short-term missions: doing it right! - Priest, Robert J. (Evangelical Missiological Society series, 2008)
Introduction / Robert J. Priest -- Connecting with long-term missions -- Short-term missions in the context of Missions Inc. / A. Scott Moreau -- Evaluating short-term missions : missiological questions from a long-term missionary / Alex G. Smith -- Complementary aspects of short-term missions and long-term missions : case studies for a win-win situation / Enoch Wan and Geoffrey Hartt -- Encountering social others -- Avoiding the ugly missionary : anthropology and short-term missions / Steven J. Ybarrola -- The myth of the blank slate : a check list for short-term missions / Miriam Adeney -- The mindful missioner / Richard Slimbach -- Forging global partnerships -- On the rhetoric of short-term missions appeals, with suggestions for team leaders / Edwin Zehner -- Friendship is forever : congregation-to-congregation relationships / C.M. Brown -- Urban church resources for short-term mission / Chin T. Wang (John) -- Women as resource brokers : STM trips, social and organizational ties, and mutual resource benefits / Kersten Bayt Priest -- Short-term missions are bigger than you think : implications for the glocal church / Rolando W. Cuellar -- Carrying out specialized ministries -- Short-term medical missions : a practitioner's perspective on effective strategies / Daniel W. O'Neill -- Children at risk in short-term missional engagement / Greg W. Burch -- Missional business professionals : the strategic and practical use of business professionals as empowered partners in short-term missions / Mark Russell -- Considering legal and liability issues in short-term missions -- Short-term missions and the law : lessons from Canada / Charles A. Cook -- Short-term missions : avoiding liability pitfalls / Michelle A. Walker-Adams and Scott Ross -- Evaluating and improving the impact of STM on participants -- Lessons from the sapling : review of quantitative research on short-term missions / Kurt Alan Ver Beek -- Researching short-term missions and paternalism / Kyeong Sook Park -- The impact of urban short-term projects on the social connections of evangelical college students / Rick Richardson -- Student sojourners and spiritual formation : understanding the intersection of cross-cultural adjustment and spiritual disorientation / Murray S. Decker -- From whatever to wherever : enhancing faith formation in young adults through short-term missions / Fran Blomberg -- Supervisors for short-term mission experiences : thinking about selection / Vicki gascho